Design Of Hugo Chavez Hospital - Omar Daragmeh; Mohammad Tammam; Mohammad Odeh (My University, 2021)
The Palestinian Venezuelan Ophthalmic Hospital - Hugo Chavez Hospital is a medical building , which is located in Turmousaya– Ramallah . The aim of the establishment of this building is to develop the health sector in Palestine by providing a hospital specializing in all eye diseases and to save the price of medical transfers abroad. This project started work in 2019 consists of a three blocks , with a total area of 8100 m 2 . In general ,the basement floors consists of kitchen, control rooms, washing , drying rooms, stores, offices and x-ray rooms , with a total area of 1980 m2 . Ground floor has Clinics, waiting, reception room, laboratory, emergency room , main educational hall, cafeteria and gift shop and procedure rooms with an area of 2088 m2 . In addition , the first floor has a dining hall, bedrooms, offices and kitchen with an area of the floor is 1920 m2 . The second floor has a break rooms, bedrooms, offices and operating rooms with an area 1918 m2 . Structural models will be analyzed and design by using computer software (ETABS 2017) , and the results will be checked by hand calculations. In addition , AutoCAD will be used in drawing sections and details. The structural elements will be designed as reinforced concrete members according to strength and serviceability criteria as specified in ACI 318-14 , for seismic design UBC 97 will be used.